ANALISIS POTENSI DAN KINERJA RETRIBUSI PASAR KABUPATEN WONOGIRI TAHUN 2008 – 2013 - Boas Benny Allan Kusuma (Jurnal Akuntansi dan Sistem Teknologi Informasi, 2015)
This study aims to determine and analyze the potency and performance of the traditional market levy and its effect on The District Originally Revenue (PAD) in Wonogiri using secondary data (time series) from 2008 up to 2013. This Study concluded: First, the calculation of the potential is known that the potential market levies increased by an average of 1,92 percent per year with the potential of each type of levy that the general market potential retribution in the category "Superfine", a potential stall fees into the category of "Retarded" and the potential for waste levies in the category of "Developing". Second, based on performance calculations known that the level of efficiency by an average of 0,89 percent per year, an average effectiveness rate of 101,14 percent per year and contribute to the PAD an average of 3,74 percent per year and is inelastic to PDRB at current prices. Keywords: autonomy, Wonogiri, PAD, PDRB, traditional market levies, potency of levies,